Islamic banking and income inequality: the role of corporate social responsibility - Nurul Muna Mohamad,; Tajul Ariffin Masron,; Risna Wijayanti,; Muslimah Mohd Jamil, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The objective of this study is to analyse whether engaging more actively in corporate social responsibility (CSR) enhances the effectiveness of Islamic banks in narrowing income inequality in the selected Organization of Islamic Cooperation (OIC) countries. Both fixed-effect and random-effect models representing static model as well as generalized method of moments approach of dynamic model are employed to estimate the sample of 24 OIC countries for the period from 2006 to 2013. The results suggest that Islamic banking has potential to reduce income inequality via Islamic financing and CSR further helps to reduce income inequality. In addition, the findings suggest that Islamic financial institutions able to reduce income inequality further if they actively engage in CSR. However, small size of CSR activities is unlikely to be effective in reducing income inequality.